Peculiarities of Social and Psychological Adaptation of Internally Displaced Persons to a New Social Environment - Aleksandrov Denys; Okhrimenko Ivan; Zarichanskyi Oleh; Yatsyshin Oleg (Insight: the psychological dimensions of society, 2025)
Restoration of the vital well-being of internally displaced persons plays a significant part in their integration into a new social environment since it determines the efficiency of their cooperation with representatives of a host community. The ability to regain the internal sensation of life satisfaction facilitates the successful adaptation of displaced persons to new living conditions, regaining their resourcefulness and assertion. For this very reason, social and psychological adaptation of internally displaced persons is among the burning issues of quality psychological counselling and social work. The purpose of this paper is to inquire into peculiarities of social and psychological adaptation of internally displaced persons to a new social environment. Methods: bibliosemantic, psychodiagnostic, the method of system analysis and generalization, mathematical and statistical method. 312 internally displaced persons took part in the investigation that was carried out in 2022–2024. Valid and reliable psychodiagnostic tools were employed. Results. It was established that the majority of internally displaced persons had a medium (moderate) level of social and psychological adaptation. Difficulties in their adaptation to new conditions of the social environment arise from the increased externality and deteriorated appreciation of others (representatives of the host party). The trends towards disinterest in life and the mismatch between set and attained goals became visible. It was found that low life satisfaction of internally displaced persons is due to their decreased adaptability, deteriorated self-acceptance and acceptance of others, externality, and the loss of dominant life stance. Discussion and Conclusions. It was established that certain deviations in indicators of propensity for escapism, submissive passiveness, and emotional discomfort can be traced against the background of the relatively typical profile of social and psychological adaptation. All this is evidence of the apparent difficulties the respondents face while adapting to the new realities of war. It is not unusual for internally displaced persons to lose interest in life, find themselves disoriented in terms of life goal setting and methods of attaining it, lose faith in themselves and their conduct. It was established that their emotional well-being is the hardest to restore; the process of self-perception is getting more complicated in the new living conditions. The research opens up space for improving social and psychological work with displaced persons. Their successful integration into a new environment suggests taking effective measures of psychological support directed at the development of a clear life stance, tolerance towards a host community, and determination enhancement.